Increasing Agrotourism Reputation through BUMDES Management - Nurirrozak, Muhamad Zahran; Maulidah, Silvana; Isaskar, Riyanti (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The Pandarejo Strawberry Barn is an agrotourism owned by the Raharjo Village-Owned Enterprises (BUMDes) in Batu City. Since its establishment in 2019, one of the focuses of the Pandarejo Strawberry Barn has been on the sale of services. The offered service is in the form of educational tourism with the concept of strawberry picking. The evolution of time shows that the business's reputation is greatly determined by the success of the business unit in serving its customers. Therefore, this research aims to determine the influence of the visiting experience on agrotourism reputation through visitor satisfaction and electronic word of mouth. This study employs a quantitative approach conducted from December 2023 to January 2024. Questionnaires were directly distributed to 230 respondents, and data were analyzed using SEM-PLS assisted by the WarpPLS 8.0 application. The research involves four variables: visiting experience, visitor satisfaction, electronic word of mouth, and agrotourism reputation. The results indicate that the visiting experience has an impact on agrotourism's reputation through visitor satisfaction and electronic word of mouth.